Iran and Oman Conflict in The Strait of Hormuz: The Potential for Cooperation - Noraini Zulkifli; Mohd Ridzuan Md Ariffin (International Journal of Education and Humanities, 2023)
The Strait of Hormuz is a vital global oil chokepoint that linked the Persian Gulf and the Gulf of Oman to the Indian Ocean and the Arabian Sea. It contains narrow international shipping lines in Iran and Oman territorial waters, and the narrowest point is only two kilometers wide. Nevertheless, major powers have devoted their interest to the Strait, especially the United States of America. This research has been conducted to analyze the conflict in the Straits of Hormuz and its implication for Iran and Oman. The objectives of this research namely 1) To identify the importance of the Strait of Hormuz, 2) To examine the causes and impacts of the conflict in the Strait of Hormuz towards Iran and Oman, and 3) To analyze the potential cooperation between Iran and Oman in handling the conflicts in the Strait of Hormuz. This research has used qualitative approaches, and secondary data were the main sources. The concepts of power and national interest have been used to explain the issues. The findings of this research are 1) The strategic location of the Strait of Hormuz became a factor of conflicts as it was the SLOC to economic activities and strategic purpose, 2) The conflicts in the Straits of Hormuz will cause the decline of economic activities, and the straits became the battlefield to both countries, and 3) Both countries should use diplomacy to settle their crisis as if it escalating, it will bring disaster to each side.